Doing Discourse Analysis in Critical Geopolitics - Martin Müller (L'Espace Politique)
This paper seeks to contribute towards a more explicit and candid discussion of the methodologies of discourse analysis within critical geopolitics. Proposing a classification along the three core dimensions of context (proximate or distal), analytic form (post-/structuralist or interpretive-explanatory) and political stance (involved or detached), it examines the ways in which critical geopolitics scholarship has understood and made use of discourse analysis. Subsequently, the paper introduces the poststructuralist discourse theory of Laclau and Mouffe, arguing that it is particularly suitable to address a number of key emerging concerns on the agenda of critical geopolitics.